Effectiveness Of Activated Carbon Of Reed (Imperata Cylindrica) As Methyl Orange Bioadsorbent with Batch Adsorption Method - Dian Ratna Suminar; Dicky Harianto; Najmi Fauziah; Dea Tri Febrian; Luthfiana Kharisma; Tifa Paramitha (Journal of Green Science and Technology, 2025)
The use of synthetic textile dyes causes environmental problems, namely the waste produced is still colored and difficult to degrade. Methyl orange is a synthetic dye in the textile industry which has low solubility in water, is difficult to degrade, has the potential to be carcinogenic and is toxic. To overcome this, adsorption can be carried out using activated carbon from reeds. This research aims to find out how active carbon of reeds is absorbed in methyl orange using the batch method with Langmuir isotherm analysis. Research methods include pretreatment of reeds, manufacture and activation of reeds carbon, testing the characteristics of activated carbon, adsorption process, and analysis of adsorption results using a UV-Vis spectrophotometer. The research was carried out by varying the concentration of methyl orange solution, adsorption time, and mass of activated carbon used. From the research, optimum conditions were obtained for the methyl orange adsorption process using reed activated carbon for 120 minutes with an activated carbon mass of 0.3 grams, a final concentration of 7.328 ppm was obtained with an initial concentration of 10 ppm, and a % adsorption of 26.72%.